Comparison the effect of stabilization and McKenzie exercises on pain, disability and lumbar multifidus muscle size in women with chronic non-specific low back pain - Maryam Sadat Larrie; Amir Houshang Bakhtiary; Rozita Hedayati; Asghar Rezasoltani; Raheb Ghorbani (Vesnu Publications, 2012)
Introduction: Low back pain may cause clinical symptoms such as: reflex inhibition and atrophy of multifidus muscles, lumbar paraspinal muscles atrophy, dysfunction and disability. The atrophy of multifidus muscles could be a main cause of recurring back pain.. Therefore, present study compared the effect of stability and McKenzie exercises on pain, disability and multifidus size in women with chronic non-specific low back pain. Materials and Methods: 60 non-athletic women  with chronic non-specific low back pain allocated in this research. They randomly and equally divided in to two experimental groups, 30 subjects (Mean ± SD age, 33.37 ± 7.92 year) in stabilization exercise group and 30 participants (Mean ± SD age, 37.00 ± 9.97 year) in McKenzie exercises group. Both groups performed exercise training for 6 weeks. The level of pain, disability, and the cross sectional area of lumbar multifidus muscle was respectively measured by visual analog scale (VAS), Ostwestry disability index and Ultrasonography imaging. These data were collected just before intervention, after 6 weeks of exercise intervention, and also at the end of 4 weeks follow-up period. Independent sample t-test was used to analyze the data and P < 0.05 was considered for statistical significance. Results: Both exercises protocols may decrease pain and disability than before exercises (P < 0.0001). The stabilization exercises may result in significant increase in L5 multifidus muscle's size (P < 0.0001), while no significant change in multifidus size was observed after McKenzie exercises (P > 0.05). Conclusion: Stabilization and McKenzie exercises may improve pain and disability in patients with chronic non-specific low back pain, while stabilization exercise results in size improvement of lumbar multifidus muscles at L5 level. Therefore stabilization exercises may be more effective to prevent recurrent chronic low back pain. Keywords: Non-specific chronic low back pain, Stabilization exercises, McKenzie exercises, Lumbar multifidus muscle